2014
DOI: 10.1002/humu.22679
|View full text |Cite
|
Sign up to set email alerts
|

Three Different Cone Opsin Gene Array Mutational Mechanisms; Genotype-Phenotype Correlation and Functional Investigation of Cone Opsin Variants

Abstract: ABSTRACT:Mutations in the OPN1LW (L-) and OPN1MW (M-)cone opsin genes underlie a spectrum of cone photoreceptor defects from stationary loss of color vision to progressive retinal degeneration. Genotypes of 22 families with a range of cone disorders were grouped into three classes: deletions of the locus control region (LCR); missense mutation (p.Cys203Arg) in an L-/Mhybrid gene; and exon 3 single-nucleotide polymorphism (SNP) interchange haplotypes in an otherwise normal gene array. Moderate-to-high myopia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(90 citation statements)
references
References 38 publications
2
86
2
Order By: Relevance
“…[21] The pathogenicity of exon 3 haplotypes was further established in a detailed study of BCM and XLCD phenotypes and genotypes in a British cohort of patients. [12] In this study, 41% of the affected males were found to have an unusual exon 3 haplotype, indicating that as a group, these haplotypes are a relatively common cause of opsin disorders and more frequent than either missense mutations or LCR deletions. LIAVA and LVAVA haplotypes were both found in the cohort in addition to a novel haplotype, MIAVA.…”
Section: The New Millenniummentioning
confidence: 53%
See 4 more Smart Citations
“…[21] The pathogenicity of exon 3 haplotypes was further established in a detailed study of BCM and XLCD phenotypes and genotypes in a British cohort of patients. [12] In this study, 41% of the affected males were found to have an unusual exon 3 haplotype, indicating that as a group, these haplotypes are a relatively common cause of opsin disorders and more frequent than either missense mutations or LCR deletions. LIAVA and LVAVA haplotypes were both found in the cohort in addition to a novel haplotype, MIAVA.…”
Section: The New Millenniummentioning
confidence: 53%
“…The IC haplotypes illustrate an unexpected genetic mechanism that appears to be a frequent cause of severe cone dysfunction in both monochromatic (BCM) and dichromatic (BED) colour vision disorders. [12,14] The effects of these haplotypes on splicing depends on the combination of variants, so some may be degenerative while others are not. LVAVA has a progressive visual phenotype that is reflected in additional damage to the S cones and rods neighbouring mutant L/M cones.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations